Analysis of digital leadership, organizational agility, and employee readiness on the effectiveness of quick service business transformation - Aulia Syafitri Yasmin; Nurbaiti Nurbaiti; Muhammad Ikhsan Harahap (Journal of Applied Business Administration, 2026)
This study aims to analyze the influence Digital Leadership, Organizational Agility, and Employee Readiness on the Effectiveness of Quick Service Business Transformation at Dimigo Café. The increasingly tight competition in the culinary industry demandscompanies to focus on creativitycompany management, the goal of which is to make things easier for consumers. This study used a quantitative approach with an associative method. The sample consisted of 50 employees, obtained using a random sampling technique. Data were analyzed using multiple linear regression after Through validity, reliability, and classical assumption tests, the results show that digital leadership has a positive and significant effect on the effectiveness of business transformation. quick service. Organizationalagilityhas a positive and significant influence on the effectiveness of quick service business transformation, Employee readiness has an influence positive and significant towardsThe effectiveness of quick service business transformation, despite the dominant influence of organizational agility, is also significant. Simultaneously, all three variables significantly contributed to the improvement of Quick Service Business Transformation. This finding confirms that a deep understanding of digital leadership, organizational agility, and relevant employee readiness are crucial factors in enhancing quick service business transformation within a company.